Physic-hydric and microbiological characteristics of three different types of soil on a rural property in Paraisópolis, MG (Research, Society and Development, 2023)
Changes in land use from native forest to agricultural or pasture areas cause changes in the physical-hydric attributes of the soil that interfere with chemical and microbiological characteristics. This study aims to evaluate the quality of three types of soil in a rural property. Soil samples were taken from areas of agricultural cultivation, pasture soil and secondary (native) forest. Were evaluated: Moisture, Water Retention Capacity, cultivable bacterial population and also producer of indole-3-acetic acid. Data were submitted to analysis of variance and the comparison of means was performed using the Tukey test (p < 0.05). The cultivation soil showed better quality in relation to the others. The attributes of the pasture soil present similarity with the soil of Secondary Forest demonstrating a good state of preservation. The soil quality indicators tested in this study are good monitoring tools.